Aβ levels in the jugular vein and high molecular weight Aβ oligomer levels in CSF can be used as biomarkers to indicate the anti-amyloid effect of IVIg for Alzheimer's disease. - Takashi Kasai (PLoS ONE, 2017)
Intravenous immunoglobulin (IVIg) has been a candidate as a potential anti-amyloid immunotherapy for Alzheimer disease (AD) because it contains anti-amyloid β (Aβ) antibodies. Although several studies with IVIg in AD have been published, changing levels of Aβ efflux from the brain, or disaggregation of Aβ species induced by immunotherapy, have not been properly investigated. Here, we carried out an open label study of therapy with IVIg in five patients with AD. We collected plasma from a peripheral vein (peripheral-plasma) and from the internal jugular vein (jugular-plasma) to estimate directly the efflux of soluble Aβ from the brain. We also measured high molecular weight (HMW) Aβ oligomers in CSF as a marker to detect disaggregated Aβ. IVIg infusions were well tolerated in the majority of cases. However, one study subject had epileptic seizures after IVIg. Levels of HMW CSF Aβ oligomers in all participants were significantly increased after IVIg. Aβ40 and Aβ42 levels in jugular-plasma were continuously or temporarily elevated after treatment in three of five patients who showed preserved cognitive function, whereas levels of those in peripheral-plasma did not correlate with reactivity to the treatment. Other conventional biomarkers including 11C-Pittsburgh compound B retention were not altered after the treatment. These findings imply that HMW Aβ oligomer levels could be a better biomarker to reflect the anti-amyloid effects of IVIg than conventional Aβ species; moreover, Aβ in jugular-plasma seems to be a more direct and precise biomarker to estimate clearance of Aβ from the brain rather than Aβ in peripheral-plasma.UMIN000022319.